2010
DOI: 10.1021/jp909681s
|View full text |Cite
|
Sign up to set email alerts
|

Study of Pentafluoroethane and its Thermal Decomposition Using UV Photoelectron Spectroscopy and Ab Initio Molecular Orbital Calculations

Abstract: The UV photoelectron spectrum of CF(3)CHF(2) has been recorded and assigned using EOM-CCSD calculations. For the first band, the adiabatic ionization energy (AIE) and vertical ionization energy (VIE) have been measured as (12.71 +/- 0.05) and (13.76 +/- 0.02) eV, respectively. The measured AIE is higher than the recommended value from state-of-the-art ab initio calculations of (12.26 +/- 0.02) eV because of a large geometry change on ionization, mainly arising from a significant increase in the C-C bond length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…21) that k 19 is about a factor of 3 below k 19,N at [Ar] = 5 Â 10 À5 mol cm À3 and T = 1300 K while it is a factor of 5 below at T = 1500 K and a factor of 10 below at 1800 K. The opposing conclusions about a dominance of the HF elimination reaction (15) from ref. 11 and about that of C-C bond breaking from the present work (and ref. 14) are easily explained by the described falloff effects.…”
Section: Decomposition Of C 2 F 5 Hsupporting
confidence: 64%
See 2 more Smart Citations
“…21) that k 19 is about a factor of 3 below k 19,N at [Ar] = 5 Â 10 À5 mol cm À3 and T = 1300 K while it is a factor of 5 below at T = 1500 K and a factor of 10 below at 1800 K. The opposing conclusions about a dominance of the HF elimination reaction (15) from ref. 11 and about that of C-C bond breaking from the present work (and ref. 14) are easily explained by the described falloff effects.…”
Section: Decomposition Of C 2 F 5 Hsupporting
confidence: 64%
“…for C 2 F 5 H in ref. [9][10][11], and for C 3 F 7 H in ref. 5 and 12. The present work extends such calculations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1,2-HF and 1,1-HF channels were identified by measuring the CF 2 CF 2 product and the adduct between CF 3 (F)­C: and trans- 2 - butene, respectively. A third unimolecular pathway from CF 3 CHF 2 has been identified from the photoelectron spectra of CF 3 H in a high-temperature flow reactor and in conventional product analysis from a flow reactor. Computational studies , also have suggested that (H atom transfer) forming CF 3 H + :CF 2 could compete with 1,1-HF and 1,2-HF elimination.…”
Section: Introductionmentioning
confidence: 99%
“…Polyhalogenated hydrocarbons including chlorofluorocarbons and bromofluorocarbons have been widely applied to industrial production, and also they result in some environmental problems. Thus, the relationship between their structure and properties has gained more and more attention . As a fundamental property of polyhalogenated hydrocarbons, their ionization potential (IP) relates to some important thermodynamic and kinetic properties and has played a significant role in theory research .…”
Section: Introductionmentioning
confidence: 99%